2020
DOI: 10.1007/s11738-020-03142-9
|View full text |Cite
|
Sign up to set email alerts
|

If phenolic compounds in the soil with buckwheat residues affect the emergence and growth of weed seedlings?

Abstract: This study was conducted to determine if common buckwheat (Fagopyrum esculentum Moench) residues affect a phenolics composition in soil, and are effective for limiting emergence, growth and metabolic changes in barnyard grass (Echinochloa crus-galli (L.) P. Beauv.), wild oat (Avena fatua L.), yellow foxtail (Setaria pumila Schult.), silky windgrass (Apera spica-venti L.), catchweed bedstraw (Galium aparine L.), scentless mayweed (Matricaria inodora L.), and tiny vetch (Vicia hirsuta L.). In the study, the resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It is assumed that allelopathy is related to a set of allelochemicals and not to a single compound (SZWED et al, 2020). These compounds interfere with neighboring plants and may cause positive physiological effects when in lower concentrations or negative ones such as germination inhibition and growth reduction (MASUM et al, 2018;LI et al, 2019).…”
Section: Similar Results Were Observed In Eleusine Indica Ageratum Co...mentioning
confidence: 99%
“…It is assumed that allelopathy is related to a set of allelochemicals and not to a single compound (SZWED et al, 2020). These compounds interfere with neighboring plants and may cause positive physiological effects when in lower concentrations or negative ones such as germination inhibition and growth reduction (MASUM et al, 2018;LI et al, 2019).…”
Section: Similar Results Were Observed In Eleusine Indica Ageratum Co...mentioning
confidence: 99%
“…The situation is similar with buckwheat. Most authors focus, however, on the potential for the limitation of the development of weeds by root secretions from this species [ 57 , 58 , 59 , 60 ]. Our own studies found the emergence of both biotypes of rye grass to be strongly limited after the addition of a higher dose of meal into the soil.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) observed that 7.5 mg mL -1 Tartary buckwheat extract reduced the growth of Galium spurium L. up to 33.7%. Recently, Szwed et al. (2020) showed that a very low percentage (1%) of the aqueous extract of 14-day common buckwheat plants was able to inhibit root development of wild oat ( Avena fatua L.), yellow foxtail ( Setaria glauca L. P.…”
Section: Using Buckwheat In Agroecology and Organic Farming For Weed ...mentioning
confidence: 99%